2018
DOI: 10.4066/biomedicalresearch.57-18-483
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of right and left heart findings according to the severity of the disease in stable chronic obstructive pulmonary disease

Abstract: Introduction: Chronic Obstructive Pulmonary Disease (COPD) is seen alongside some systemic diseases that result in impaired functional capacity, worsening dyspnea, decreased health-related quality of life and increased mortality. Cardiovascular diseases, considering their effect on mortality, play an important role in such diseases. Objective: The aim of this study to evaluate the cardiac changes that develop secondary to COPD and attempt to identify any correlation between the severities of the disease determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Contrary to our study, Chaudhary and Shrimali reported majority (80%) chest radiograph suggestive of features of emphysema and 68% chronic bronchitis [25]. Other features on chest radiograph in our study were cardiomegaly (36.1%) and pulmonary hypertension (prominent pulmonary conus / prominent right descending pulmonary artery>16mm) in 19.7 % of the patients.…”
Section: Chest Radiographcontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our study, Chaudhary and Shrimali reported majority (80%) chest radiograph suggestive of features of emphysema and 68% chronic bronchitis [25]. Other features on chest radiograph in our study were cardiomegaly (36.1%) and pulmonary hypertension (prominent pulmonary conus / prominent right descending pulmonary artery>16mm) in 19.7 % of the patients.…”
Section: Chest Radiographcontrasting
confidence: 99%
“…Similar distribution was observed in many studies. The distribution of participants in study by Chaudhary and Shrimali was also similar with severe COPD (62%), moderate COPD (34%) and mild COPD (4%) [25]. In the study by Suma et al, 60% of the patients had severe airflow obstruction, 36% had moderate and 4% had mild disease [26].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation